Effect of Cationic Lipid Type in Folate-PEG-Modified Cationic Liposomes on Folate Receptor-Mediated siRNA Transfection in Tumor Cells - Yoshiyuki Hattori; Satono Shimizu; Kei-ichi Ozaki; Hiraku Onishi (MDPI AG, 2019)
In this study, we examined the effect of cationic lipid type in folate (FA)-polyethylene glycol (PEG)-modified cationic liposomes on gene-silencing effects in tumor cells using cationic liposomes/siRNA complexes (siRNA lipoplexes). We used three types of cationic cholesterol derivatives, cholesteryl (3-((2-hydroxyethyl)amino)propyl)carbamate hydroiodide (HAPC-Chol), N-(2-(2-hydroxyethylamino)ethyl)cholesteryl-3-carboxamide (OH-Chol), and cholesteryl (2-((2-hydroxyethyl)amino)ethyl)carbamate (OH-C-Chol), and we prepared three types of FA-PEG-modified siRNA lipoplexes. The modification of cationic liposomes with 1–2 mol % PEG-lipid abolished the gene-silencing effect in human nasopharyngeal tumor KB cells, which overexpress the FA receptor (FR). In contrast, FA-PEG-modification of cationic liposomes restored gene-silencing activity regardless of the cationic lipid type in cationic liposomes. However, the optimal amount of PEG-lipid and FA-PEG-lipid in cationic liposomes for selective gene silencing and cellular uptake were different among the three types of cationic liposomes. Furthermore, in vitro transfection of polo-like kinase 1 (PLK1) siRNA by FA-PEG-modified liposomes exhibited strong cytotoxicity in KB cells, compared with PEG-modified liposomes; however, in in vivo therapy, intratumoral injection of PEG-modified PLK1 siRNA lipoplexes inhibited tumor growth of KB xenografts, as well as that of FA-PEG-modified PLK1 siRNA lipoplexes. From these results, the optimal formulation of PEG- and FA-PEG-modified liposomes for FR-selective gene silencing might be different between in vitro and in vivo transfection.